An Efficient General Family of Estimators for Population Mean in the Presence of Non-Response - Thanapanang Rachokarn; Nuanpan Lawson (Journal of Mathematical and Fundamental Sciences, 2017)
This paper presents a new general family of estimators to estimate the population mean of study variable y in the presence of non-response when utilizing a known coefficient of variation of study variable y. The expressions for bias, mean squared error (MSE), and minimum mean squared error (MMSE) of the proposed family of estimators are derived up to the first degree of approximation. In addition, a numerical example and a simulation study are presented to explain the performance of the proposed estimators. It was shown that the proposed estimators perform better compared to all other relevant estimators.